A Partial Reedition of 4Q26a (4QLeviticuse): A New Fragment and a Reinterpretation - Tigchelaar, Eibert J. C. (Dead Sea discoveries, 2014)
A new identification of a 4Q26a (4QLeviticuse) fragment, as well as the reinterpretation on the basis of new photographs of 4Q26a frag. 8 as preserving Lev 20:2–4, rather than Lev 22:4–6, requires a reedition of two sections of the manuscript, and enables a partial material reconstruction of the scroll.